Problems on chromatic polynomials of hypergraphs - Ruixue Zhang; Fengming Dong (Electronic Journal of Graph Theory and Applications (EJGTA), 2020)
Chromatic polynomials of graphs have been studied extensively for around one century. The concept of chromatic polynomial of a hypergraph is a natural extension of chromatic polynomial of a graph. It also has been studied for more than 30 years. This short article will focus on introducing some important open prblems on chromatic polynomials of hypergraphs.